Posture characterization based on time and frequency domains parameters for erector spine SEMG signal - Shobaki, Mohammed M.; Abdul Malik, Noreha; Khan, Sheroz; Nordin, Anis Nurashikin; Haider, Samnan; Khairul Azami, Sidek (IEEE, 2014)
This work is based on obtaining surface EMG signals from lower back muscles using a data logger by Pico Log technology. The electrodes used are Ag/AgCl and applied after a clean surface washing by alcohol of erector spine muscle for a subject under two posture conditions. The conditioning circuit used in this paper is selectively choosing the 20-500Hz dominant frequency range and 0.4 to 2.4 Volts in amplitude. The data on signals are transported onto a PC into Excel file for processing its FFT representative of the target posture condition. The bow condition shows four times larger in magnitude of FFT compared to that of standing condition over a similar frequency range of 50-220Hz. The utility of the conditioning circuit is justified by reducing the power frequency noise to negligible level. The utility of this research work has potential in clinical diagnostic applications.